PENGEMBANGAN BOOKLET KEANEKARAGAMAN POHON BERBASIS PENELITIAN SEBAGAI BAHAN PENGAYAAN KONSEP KEANEKARAGAMAN HAYATI DI SMA - Siti Nur Latifah, Hardiansyah, Mahrudin (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
The existence of living things in a habitat is something that can be used as an object of learning, moreover the object used is a local potential area that must be introduced to students. One of the objects that can be studied both in the form of observed objects, ways of life, benefits and even their preservation is trees. This study aims to describe the validity and practicality of the Tree Diversity Booklet in the Mangrove Forest Area of ​​Sungai Rasau Village, Tanah Laut District. This research is a development research using secondary data. The enrichment material developed is in the form of a booklet with the development method referring to Tessmer's Formative Evaluation. The validity of the booklet was tested by 3 validators, while the practicality test was tested on 5 students in XI grade. The results of the development of booklet teaching materials in the validation test were declared valid with an average validity score of 87.3%. In the practicality test by 5 SMAN 1 Tamban students, a score of 3.38 was obtained with good criteria. So that the booklet teaching materials can be used as material for enriching the concept of biodiversity in high school.